Estrategias de comercialización en el centro de medicina “A Lo Natural” de la parroquia San Juan, periodo 2022 - Vargas López, José Antonio (2023)
The present project consolidates a study of reference to marketing strategies in the "a lo natural" medicine center of the San Juan parish, for the period 2022, this considering the problem that the company faces is a sales deficit in the period 2022 both in products and medical consultations because they are not applying efficient trade strategies due to lack of knowledge in this very important field such as marketing. Therefore, a research work is carried out that aims to create a marketing plan with business strategies that help increase sales in the microenterprise medicine center "a lo natural", where you want to capture the attention of the public. audience and create a portfolio of new customers and retain existing ones. The objective of marketing strategies is to promote the sale of a line of products already known to consumers, which is achieved through techniques that allow, in the first instance, to attract the attention of the public. In this study, the deductive method will be used in order to reach correct conclusions about the case, therefore, an interview with the owner of the naturist center will be used as a data collection method, with the purpose of having information available from a direct source. , thus allowing to know the particularities of the case, to analyze qualitative data so that it is possible to deepen the study of the situation raised and valid arguments are contributed that allow validating improvement alternatives for the business.